(untitled) (Journal of Mechanical Engineering, 2008)
Durability and tribological properties of thermally sprayed WC-Cr-Ni cermet coating were investigated experimentally under full film and partial elastohydrodynamic lubrication (EHL) conditions. By means of the high energy type flame spraying (Hi-HVOF) method, the coating was formed onto the axially ground and circumferentially ground roller specimens made of thermally refined carbon steel. The WC cermet coated steel roller was mated with the carburized hardened smooth steel roller under full film EHL condition and carburized hardened rough steel roller under partial EHL condition. It was found that, in general, the coating on the circumferentially ground substrate shows a lower durability compared with that on the axially ground substrate and this difference appears more distinctly for the higher contact pressure for both full film and partial EHL conditions. It was also found that there are significant differences in the tribological properties of WC cermet coating depending on the contact pressure. In addition, depending on the lubrication condition, remarkable differences in the tribological properties were found. Keywords: WC cermet, Full film EHL, Partial EHL, Durability, Tribological propertiesÂ Journal of Mechanical Engineering Vol.36 Dec. 2006 pp.38-43 DOI = 10.3329/jme.v36i0.809